PENGARUH PENGALAMAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI - Heriyanto Heriyanto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
The results showed that work experience and motivation had a positive and significant effect on the performance of employees in the Development Section of the East Kutai Regency Secretariat. Based on the results of the determination coefficient that the relationship of variable Y (performance) is strongly influenced by variables X1 (work experience) and X2 (motivation) of 91.9% and the remaining 8.1% is influenced by other factors not examined in this study. Partial test of work experience variables (X1) on employee performance (Y) based on the results of the analysis obtained t count of 9.8886 with significant (0.00 <0.05) so that there is a positive and significant influence between work experience and employee performance and motivation variable (X2) on performance employees (Y) based on the results of the analysis obtained t count value of 3.139 has a positive and significant effect this can be seen from the significant value (0.003 <0.05) which means that if motivation is increased then the performance of employees will increase. The partial test results show that the most dominant work experience variables affect the performance of employees in the Development Section of the East Kutai Regency Secretariat.\